Efficient Metal-Free Synthesis of Heterotriarylmethanes by 1,4-Addition of Benzofuran Azadienes - Huang, Hong-Li; Li, Shan; Lv, Yong-Zheng; Shi, Ya-Qian; Liu, Chang-Bo; Peng, Zhongzhong; Gao, Fei (Synlett, 2024)
A novel and efficient method has been established for synthesizing a variety of heterotriarylmethanes with good yields by employing a metal-free self-coupling reaction of benzofuran azadienes. The involvement of t-BuONa is essential in this process. Remarkably, this technique boasts mild reaction conditions and exceptional compatibility with various functional groups, rendering it a versatile and invaluable asset in the realm of organic synthesis.
Keywords: metal-free synthesis; heterocycles; benzofuran azadienes; heterotriarylmethanes